Microscopic model for switching kinetics in organic ferroelectrics following the Merz law - Cornelissen, Tim D.; Urbanavičiūtė, Indrė; Kemerink, Martijn (Physical review, 2020)
From an application perspective, one of the most important parameters of a ferroelectric is its switching time, and understanding its limiting factors is key to improve device performance. While there is a variety of competing models for switching kinetics in realistic (disordered) ferroelectrics, they are often merely descriptive and provide little insight into the underlying microscopic mechanisms. This holds in particular for the classical Merz law, which describes the commonly observed exponential field dependence of the switching time. Here, we investigate the switching kinetics in the archetypical molecular ferroelectric trialkylbenzene-1,3,5- tricarboxamide using an electrostatic kinetic Monte Carlo model. The simulated field dependence follows the Merz law, which shows that a simple system of interacting dipoles is sufficient to obtain this behavior, even without explicitly considering domain walls or defects that are commonly thought to be involved in the emergence of the Merz law. Through a detailed analysis of the nucleation process, we can relate the macroscopic switching time to the microscopic nucleation energy barrier, which in turn is related to a field-dependent nucleus size. Finally, we use the acquired insight into the nucleation process to derive the Merz law from the theory of thermally activated nucleation-limited switching. This analytical model provides a physically transparent description of the switching kinetics in both experiments and simulations.
Gesehen am 22.03.2021